Abnormal Presentation of Foster Kennedy Syndrome Due to Schwannoma of Optic Nerve - Tuhina Mishra; Smita Singh; Ajay Kumar Shukla (Delhi Journal of Ophthalmology)
Foster Kennedy syndrome (FKS) is a rare neuro-ophthalmic syndrome that occurs because of an intracranial mass, most commonly a tumor. As a result of the intracranial mass, the patient develops optic atrophy on the same side of the lesion and papilledema on the contralateral side. In this case report, we present the case of a 25-year-old male who presented to the ophthalmology clinic with unusual complaints of proptosis and diminution of vision in the right eye. A diagnosis of schwannoma of the optic nerve was made on magnetic resonance imaging retrospectively after diagnosing FKS in the patient clinically.